The differentiated impacts of urbanisation on lake communities in Bengaluru, India. Issue 1 (2nd January 2021) - Sen, Amrita; Nagendra, Harini
ABSTRACT: This research assesses the differentiated impacts of urbanisation on communities of Bengaluru, who earlier inhabited agrarian and rural commons landscapes. Drawing on empirical observations from residents of peri-urban erstwhile villages of Bengaluru located next to lakes, we examine changes in their social-ecological practices, linked to the urban transformation of these landscapes. Urbanisation has transformed once-rural landscapes into fast growing urban areas at peripheries of Bengaluru. We show that impacts of urban transition are not homogenous or representative of uniform trends, but diverse, shaped by differing power relationships that manifest themselves within the Indian caste hierarchy. Urban transitions, while undoubtedly bringing about disconnects with the social-ecological landscape, have been disenfranchising in some aspects but emancipatory in other ways, liberating underprivileged castes from the worst practices of exploitation. We argue that urbanisation experiences vary, depending on the past and opens up prospects for challenging the received understanding of urbanisation, through individual experiences.